‘Cendekia Bitara’ award honours outstanding researchers and lecturers - UMP, PNC
Universiti Malaysia Pahang (UMP) Chancellor His Highness Tengku Mahkota of Pahang Tengku Abdullah Al-Haj Ibni Sultan Haji Ahmad Shah Al-Musta’in Billah presented awards to 33 recipients comprising academicians during the ‘Cendekia Bitara (Incomparable Intellectuals) 2012’ Award ceremony held at Zenith Hotel, Kuantan on April 19, 2013.